Principal component analysis (PCA) as a genetic diversity tool to understand the variation of rice mutant culture - S. Palaniyappan1, P. Arunachalam1*, S. Banumathy1 and S. Muthuramu2 (Electronic Journal of Plant Breeding)
The current research experiment was carried out to analyze the genetic variations among rice mutants and homozygous lines from cross derivatives by principal component analysis (PCA). The PCA results had shown the first five PCs accounted 83.20 per cent of total genetic variation. The thirty six rice genotypes were formed into four groups. Among the variables studied, hundred grain weight (0.907), grain length (0.837), grain width (0.799) and plant height on 50th day (0.617) positively contributed to 29.15 % variation of first PC. Whereas, days to maturity (0.708), days to fifty percent flowering (0.643) and flag leaf breadth (0.609) contributed mostly for 21.60 percent variation of second PC. More precisely, the grouping revealed that the EMS mutants of Anna (R) 4 were potentially mutated not only for the grain type and also for yield related traits such as flag leaf length and breadth, panicle length, plant height. The genotypes grouped 1 and 4 had potential to select higher grain yield with improved grain quality suitable for rainfed condition.